Decoupling Study of Melt Polycondensation of Polycarbonate: Experimental and Modeling of Reaction Kinetics and Mass Transfer in Thin Films Polycondensation Process. Issue 3 (15th March 2018) - Bi, Fenglei; Qiu, Xiaoyi; Xi, Zhenhao; Zhao, Ling; Feng, Lianfang
Abstract: During the melt polycondensation process of polycarbonate, reaction and mass transfer are deeply coupled owing to relatively high melt viscosity. In this work, the polycondensation reaction kinetics and mass transfer behavior of volatile phenol are decoupling studied in detail by using thin‐film experiments with 250–280 °C, 10–1000 Pa and 0.085–0.68 mm film thickness. A realistic apparent rate model coupled the reaction kinetics with thermodynamic equilibrium and diffusion behavior is developed to describe the polycondensation process, while the diffusion characteristic of small molecule (phenol) is further obtained based on penetration theory. The obtained polycondensation equilibrium constant ranges from 0.3 to 0.55, while the activation energy and pre‐exponential factor of temperature‐dependent diffusion coefficients of phenol are 87.9 kJ mol −1 and 5.08 × 10 2 m 2 s −1, respectively. It is also observed that the overall apparent rate of polycarbonate (PC) polycondensation process increases with higher temperature, lower pressure, and thinner film thickness. Coupling the reaction kinetics with mass transfer, the predictions of the realistic apparent rate model are in quite satisfactory agreement with experimental data. Abstract : An understanding of the physical and chemical processes involved in melt polycondensation of polycarbonate with relative high melt viscosity is of fundamental significance. In this work, a realistic apparent rate model coupled the reaction kinetics with diffusion behavior is developed to describe the polycondensation process, while the diffusivity of the small molecule phenol is obtained based on penetration theory.